484. UPFRONT SURGERY VERSUS PREOPERATIVE TREATMENT FOR PATIENTS AGED 80 YEARS OLDER WITH ESOPHAGEAL CANCER. (24th September 2022) - Sakurai, Toru; Utsunomiya, Daichi; Kubo, Kentaro; Kanematsu, Kyohei; Kurita, Daisuke; Ishiyama, Koshiro; Oguma, Junya; Daiko, Hiroyuki
Abstract: In recent years, with the aging of the population, there have been more opportunities to operate on very elderly esophageal cancer patients over the age of 80. The safety of neoadjuvant chemotherapy has become the standard, but for very elderly patients is not clear. In our hospital, it is selected if general condition is acceptable. This time, we examined cases of very elderly esophageal cancer patients aged over 80 years performed esophagectomy at our hospital. The subjects were 28 patients aged 80 years or older who underwent esophagectomy at our hospital for advanced esophageal cancer from January 2017 to December 2020. A retrospective study was performed by dividing into the upfront surgery group (S) and the preoperative treatment group (Neo: neoadjuvant chemotherapy group, preoperative chemoradiation group, salvage surgery group). The primary endpoints were recurrence rate and recurrence-free survival (month), and the secondary endpoints were preoperative adverse event incidence, R0 achievement rate, and perioperative complication rate in the preoperative treatment group. Median age is 82 years (range: 80-89 years). S/Neo= 21/7 cases. Chemotherapy were DCF: 1 case, FOLFOX: 2 cases, FP: 2 cases, CDDP + VP: 1 case. Preoperative adverse event incidence of Grade 3 or higher was 14.2%. The R0 achievement rate was 90%/100% (S/Neo, p= 0.442; t-test). Perioperative complications rate of Clavien-Dindo IIIa or higher was 33.3%/71.4% (S/Neo, p= 0.083; t test). The recurrence rate was 57.1%/14.2% (S/Neo), which were significantly lower in the Neo than in the S(p= 0.049; Logistic regression model). The median recurrence-free survival was 13 months in the S and 10 months in the Neo. It is necessary to select a treatment method that balances curative and postoperative QOL for the elderly based on organ function, tumor factors, social background, etc. Since it is difficult to use CDDP for very elderly patients, FOLFOX is the first choice at our hospital. Operation techniques such as less invasive mediastinoscopic and two-staged surgery are selected. From the results of this study, preoperative treatment may reduce the recurrence rate.